Moral and Religious Mental Development of TNI Soldiers Based on Spiritual Approach from the Perspective of Hizbiyyah Da’wah - Fajar, Dadang Ahmad; Muhlas, Muhlas (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This research aims to identify mental development programs at the TNI Pusbintal with a spiritual approach. The research approach used in this research is a qualitative approach with data collection techniques in the form of interviews and literature studies. The research results show that the moral and mental development of TNI soldiers carried out by the TNI Pusbintal on a spiritual basis plays a vital role in shaping the moral and mental characteristics of TNI soldiers. The spiritual-based coaching techniques used are prayer, dhikr and meditation. These three techniques are not only explained in material form but are also applied in the daily lives of TNI soldiers when they carry out their duties. The above shows the role of mental development for the TNI based on al-Islamiyah da'wah. Mental training within the TNI has apparent legal force and carries sanctions for violators. So, mental development in religious practice further shows the role of the TNI Pusbintal as one of the constructs of al-Islamiyah da'wah. From a da'wah perspective, the TNI Pusbintal can be categorized as a da'wah institution that carries out institutional da'wah or hizbiyyah da'wah. This institution is vital to strengthening the mentality and morale of TNI soldiers based on Islamic spiritual values. Thus, it will strengthen the TNI, which is not only an educational institution that produces strong soldiers but also has a depth of spirituality in carrying out its duties to maintain national security and defence.